A Descriptive Study on Youth and the Nepalese Labour Market - Gelal, Prashu Ram (The Batuk, 2022)
Workers aged between 15 and 24 are considered as youth workers. The major challenge related to employment of young people is to stay in low productivity with unpaid position or the opportunity to move for foreign employment. Nepal is not an exception to this trend. This study was carried out to describe the legal framework of Nepal regarding youth workers. As per Central Bureau of Statistics (CBS), about 0.5 million youths enter Nepalese market every year. It is found that the unemployment rate of young works in Nepal is 19% compared to 2.7% for the whole population. Though the labour and trade union rights in Nepal are addressed at satisfactory level, the implementation status still needs high attention. Due to unavailability of appropriate job with fair pay, majority of them seek foreign employment in their early age. Reasonable wage rate, social protection, and labour right of the country in line with international conventions play in shaping the utilization and movement of youth workers. Nepal needs to work a lot on satisfaction of youth worker for the national prosperity.